Enabling Argyrodite Sulfides as Superb Solid‐State Electrolyte with Remarkable Interfacial Stability Against Electrodes - Xu, Hongjie; Cao, Guoqin; Shen, Yonglong; Yu, Yuran; Hu, Junhua; Wang, Zhuo; Shao, Guosheng (Energy & environmental materials (Hoboken, N.J.), 2022)
While argyrodite sulfides are getting more and more attention as highly promising solid‐state electrolytes (SSEs) for solid batteries, they also suffer from the typical sulfide setbacks such as poor electrochemical compatibility with Li anode and high‐voltage cathodes and serious sensitivity to humid air, which hinders their practical applications. Herein, we have devised an effective strategy to overcome these challenging shortcomings through modification of chalcogen chemistry under the guidance of theoretical modeling. The resultant Li6.25PS4O1.25Cl0.75 delivered excellent electrochemical compatibility with both pure Li anode and high‐voltage LiCoO2 cathode, without compromising the superb ionic conductivity of the pristine sulfide. Furthermore, the current SSE also exhibited highly improved stability to oxygen and humidity, with further advantage being more insulating to electrons. The remarkably enhanced compatibility with electrodes is attributed to in situ formation of helpful electrolyte–electrode interphases. The formation of in situ anode–electrolyte interphase (AEI) enabled stable Li plating/stripping in the Li|Li6.25PS4O1.25Cl0.75|Li symmetric cells at a high current density up to 1 mA cm−2 over 200 h and 2 mA cm−2 for another 100 h. The in situ amorphous nano‐film cathode–electrolyte interphase (CEI) facilitated protection of the SSE from decomposition at elevated voltage. Consequently, the synergistic effect of AEI and CEI helped the LiCoO2|Li6.25PS4O1.25Cl0.75|Li full‐battery cell to achieve markedly better cycling stability than that using the pristine Li6PS5Cl as SSE, at a high area loading of the active cathode material (4 mg cm−2) in type‐2032 coin cells. This work is to add a desirable SSE in the argyrodite sulfide family, so that high‐performance solid battery cells could be fabricated without the usual need of strict control of the ambient atmosphere. Oxygen alloying for high‐performance argyrodite sulfide electrolyte: remarkably widended electrochemical window, highly protective amorphous electrolyte‐electrode interphases, and high lithium ion conductivity maintained.